2007
DOI: 10.1111/j.1365-2265.2007.03048.x
|View full text |Cite
|
Sign up to set email alerts
|

Reference range of thyroid hormones in normal Indian school‐age children

Abstract: This study provides mean reference intervals for FT3, FT4 and TSH for each year of life for both the sexes separately using strict exclusion criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 28 publications
4
23
0
4
Order By: Relevance
“…We have previously suggested that this phenomenon could be an in vivo reflection of the previously reported increase in the in vitro activity of deiodinases in response to increasing TSH concentrations (3). Another sidefinding was the difference between the genders in thyroid hormone levels that is in agreement with one previous study and differs somewhat from the two others (10,11,12). From our results (Tables 1 and 2), it appears that beyond age 40, the effect of TSH to increase T3 production from T4 becomes less pronounced and may be completely abolished in the elderly.…”
Section: Discussionsupporting
confidence: 63%
“…We have previously suggested that this phenomenon could be an in vivo reflection of the previously reported increase in the in vitro activity of deiodinases in response to increasing TSH concentrations (3). Another sidefinding was the difference between the genders in thyroid hormone levels that is in agreement with one previous study and differs somewhat from the two others (10,11,12). From our results (Tables 1 and 2), it appears that beyond age 40, the effect of TSH to increase T3 production from T4 becomes less pronounced and may be completely abolished in the elderly.…”
Section: Discussionsupporting
confidence: 63%
“…The study subjects were categorized as euthyroid, subclinical hypothyroidism, overt hypothyroidism, subclinical hyperthyroidism, and overt hyperthyroidism [7,10] ; the values of TSH are mentioned in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Marwaha ve arkadaşlarının Hindistan'da yapılmış iki ça-lışmasında beş ile onaltı yaş arası çocuklarda TSH'nın ortalama değeri 3,17 mIU/L, 97 persentil değeri 7,5 mIU/L ölçüldüğü belirtilmiştir [11][12].…”
Section: şEkil 1 çOcuklarda Hipotiroidizmin Durumuunclassified
“…Genel olarak yayınlarda ise çocuklarda %2 erişkinlerde ise %1-10 arasın-da tespit edilmiştir [4,13,16]. Hindistan'da Marwaha'nın 39961 çocuk ile yaptığı çalışmada %6,1 SH tespit edilmiş-tir [12]. Lazar ve ark.…”
Section: Epidemiyolojiunclassified